Accounting Vocational Students' Perception Towards the English Project in Curriculum Merdeka - Ainin Sofiya Septiana; Festi Himatu Karima; Prita Nusanti (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
The project-based learning used in the curriculum merdeka to help students improve their soft skills in line with the traits of the Pancasila Student Profile is one of the features that sets it apart from the previous curriculum the most. This study will discuss how accounting students at Semarang's vocational schools experienced project-based learning in an English class initiated during the second semester of the 2022–2023 academic year. This study, conducted on accounting students in the tenth grade at a vocational high school in Semarang that was implementing the curriculum merdeka for the first time, included 36 students as subjects. Using survey from quantitative research, this study used a Likert scale with 13 questionnaires to determine their feelings about project-based learning in the curriculum merdeka for English class. We can conclude from this study's findings that all accounting students positively perceive English lessons with project-based learning. So, teachers can consider using Project-Based Learning in the curriculum merdeka according to students' perceptions. The scope of accounting students at Semarang's vocational schools was the subject of this study.